A Glutathione Activatable Ion Channel Induces Apoptosis in Cancer Cells by Depleting Intracellular Glutathione Levels. (12th March 2020) - Malla, Javid Ahmad; Umesh, Rintu M.; Yousf, Saleem; Mane, Shrunal; Sharma, Shilpy; Lahiri, Mayurika; Talukdar, Pinaki
Abstract: Cancer cells use elevated glutathione (GSH) levels as an inner line of defense to evade apoptosis and develop drug resistance. In this study, we describe a novel 2, 4‐nitrobenzenesulfonyl (DNS) protected 2‐hydroxyisophthalamide system that exploits GSH for its activation into free 2‐hydroxyisophthalamide forming supramolecular M + /Cl − channels. Better permeation of the DNS protected compound into MCF‐7 cells compared to the free 2‐hydroxyisophthalamide and GSH‐activatable ion transport resulted in higher cytotoxicity, which was associated with increased oxidative stress that further reduced the intracellular GSH levels and altered mitochondrial membrane permeability leading to the induction of the intrinsic apoptosis pathway. The GSH‐activatable transport‐mediated cell death was further validated in rat insulinoma cells ( INS‐1E ); wherein the intracellular GSH levels showed a direct correlation to the resulting cytotoxicity. Lastly, the active compound was found to restrict the growth and proliferation of 3D spheroids of MCF‐7 cells with efficiency similar to that of the anticancer drug doxorubicin. Abstract : Krebszellen nutzen erhöhte Glutathion‐Spiegel als Verteidigung gegen Apoptose und zur Entwicklung von Wirkstoffresistenz. Ein 2, 4‐Nitrobenzolsulfonyl‐geschütztes 2‐Hydroxyisophthalamid wird beschrieben, das die intrazelluläre Glutathion‐Verteidigung durch Aktivierung von Ionenkanälen schwächt und zur Produktion reaktiver Sauerstoffspezies und Apoptose führt.